LO47: Use of C-reactive protein can safely decrease the number of emergency department patients with sepsis who require blood cultures. (15th May 2017) - Stenstrom, R.; Choi, J.; Grafstein, E.; Kawano, T.; Sweet, D.; Bischoff, T.; Leung, V.; Halim, S.
Abstract : Introduction: Sepsis protocols call for the acquisition of blood cultures in septic emergency department (ED) patients.However, the criteria for blood cultures are vague, they are costly, only positive 8-12% of the time, with up to half of these being false positives. The objective of this study was to establish if positive blood cultures could be excluded in low-risk sepsis patients with levels of CRP below 20 ml/L.Methods: This was a multicenter prospective cohort study of 765 ED patients at St Paul's and Mount St Joseph's hospitals in Vancouver with sepsis (2 or more SIRS criteria and infection) and none of: immuncompromised, injection drug use, indwelling vascular device or septic shock (SBP<90 mmhg). Consecutive patients with sepsis had CRP and blood cultures obtained at the same time.OUTCOMES. True positive blood cultures, false positive blood cultures, positive blood cultures that changed patient management. True and false positive blood cultures were based on Infectious Disease Society of America Guidelines, and change in management was defined as change in type or length of antibiotic therapy and was blindly adjudicated by a medical microbiologist.Results: 765 ED patients with sepsis met inclusion criteria. Mean age was 48.3 years and 57% were male. Blood cultures were positive in 99/765 (12.9%) subjects, of which 19 were false positive (19.2%). CRP was >20 mg/L in 595/765 (77.8%) of patients. Of 170 subjects with a CRP<20 mg/L, 3 had a positive blood culture (1.8%; 95% CI 0.1%- 5%). Management was not changed in any patient with a positive blood culture and CRP level<20 mg/L. Of 19 subjects with a false positive blood culture, CRP was <20 mg/L for 6 (31.6%).Conclusion: In this cohort of low-risk sepsis patients, based on a CRP of <20 mg/L, acquisition of blood cultures could be safely avoided in 22.2% of patients, at significant savings to the health care system.